Resistance to Dislodgement of REBILDA® Post System to Intraradicular Dentin - Ross DDS, Daphne (2017)
Currently there is controversy in the literature about clinical and adhesive effectiveness with respect to adhesive systems aimed to  root reinforcement. Thus, the objective of this study was to evaluate the Push-Out bond strength between the Rebilda® post system and the intraradicular dentine. Thus, 28 unirradicular teeth were used, cut and standardized in 16 mm. The root segments were submitted to endodontic treatment; and then randomly divided into two groups, Group 1 (n = 14): Rebilda® DC + Futurabond DC; Group 2 (n = 14): RelyX ARC + Adper Scothbond Multipurpose Plus. Ten specimens from each group were submitted  to the Push-Out Test. The remaining 4 specimens from each group were prepared for Scanning Electron Microscopy (SEM) in order to evaluate the formation of resinous extensions at the post-cement-dentin interface. Group 2 showed better results when compared to Group 1 regarding bond strength and in formation of resinous extensions or tags, but there was no statistically significant difference (p>0.05). It was concluded that the REBILDA® Post System promotes adequate bond strength to intraradicular dentin.